Dimethylprolinol Versus Diphenylprolinol in CuBr2-Catalyzed Enantioselective Allenylation of Terminal Alkynols - Ma, Dengke; Duan, Xinyu; Fu, Chunling; Huang, Xin; Ma, Shengming (Synthesis, 2018)
The CuBr2-catalyzed enantioselective allenylation of terminal alkynols with carbon chains of different lengths has been developed. Compared with (S)-α,α-diphenylprolinol, the reaction using (S)-α,α-dimethylprolinol as the chiral amine afforded optically active 1,3-disubstuted allenols with higher ee-values. Both aliphatic and aromatic aldehydes could be applied. The naturally occurring phlomic acid was synthesized in four steps from commercially available hex-5-yn-1-ol.
Keywords: CuBr2; enantioselective allenylation; terminal alkynols; (S)-α,α-diphenylprolinol; (S)-α,α-dimethylprolinol; phlomic acid